Addressing obstetric violence: a scoping review of interventions in healthcare and their impact on maternal care quality - Yalley, Abena Asefuaba; Jarašiūnaitė-Fedosejeva, Gabija; Kömürcü-Akik, Burcu; de Abreu, Liliana (Frontiers in Public Health, 2024)
Background The mistreatment and abuse of women during childbirth have been recognized as a major global health challenge, impeding facility-based delivery and contributing to the high maternal mortalities globally. The World Health Organization has specifically called for interventions to deal with obstetric violence. This scoping review consolidates the existing literature on interventions aimed at reducing obstetric violence and synthesizes existing knowledge on their impact in promoting respectful maternity care. Methodology Thirteen electronic databases were searched for relevant articles from January 2001 to March 2023. A total of 863 records were identified, and 72 full-text articles were retrieved for further screening. The review includes 16 studies, particularly from low- and middle-income countries, with interventions implemented at medical facilities and involving both women and healthcare providers. Eight of the studies were quantitative, three were qualitative and five used a mixed-methods approach. Findings The results reveal a promising trend in reducing obstetric violence through various interventions. Ten different types of interventions were identified, highlighting strategies to improve the quality of maternity care and enhance patient-centered care. Improved patient-provider communication skills, increased privacy measures, and reduced abuse and mistreatment emerged as common themes. Enhanced communication skills, including open discussions and the right to be informed, were crucial in reducing obstetric violence. Privacy measures, such as separate rooms, curtains, and birth companions effectively decreased incidents of non-confidential care. General abuse and mistreatment, including physical abuse and neglect, were also reduced, leading to improved perceptions of respectful care during childbirth. Conclusion Overall, the interventions had a favorable impact on obstetric violence reduction and women’s childbirth experiences. However, despite promising results, obstetric violence remains prevalent worldwide, necessitating more efforts to implement effective interventions. To the best of our knowledge, this is the first scoping review on obstetric violence interventions, providing a comprehensive overview of the state of the art. We suggest that further research is needed to explore new interventions, particularly gender-sensitive interventions, to contribute to a growing body of knowledge on the prevention of obstetric violence.